Critical Analysis of Nursing Practices in Bridging Clinical Care and Administrative Leadership - balharith, Ali abdullah mohammed; AlQahtani, Nayef Masoud Ali; Aloufi, Sami Adburrahman Ayed; Alharbi, Saif Awad Awadallh; Alshammari, Naif Fayez Naif; Alahmadi, Bandar Salim M; Althubyani, Fahad Khalil Masad; Alsaedi, Fahd Hamdan; Al saedi, Tareq Hamed; Alsahli, Mohammed Saud (Journal of Ecohumanism, 2024)
For some time, nursing work has assumed a more complex function in healthcare; specifically, work has more administrative responsibilities. Therefore, This shift has benefits that allow for the evolution of professional practice and challenges the nurses' attempt to narrow the gap between clinical floors and leadership positions in various organizations. This paper, therefore, provides a critical review of nursing interventions, factors related to nurse leaders and followership, and organizational, patient and contextual outcomes. The review also presents major categories: collaboration by nurse leaders, change leadership and patient care outcomes. Moreover, it investigates the challenges concerning integrating the clinical leadership function and gives recommendations for improving the performance of the nurse leaders who perform two different roles. The results evidence how different leadership skills ought to be developed in nurses to reform the health systems and enhance interprofessional relations and patient care.